Effect of Oral Chinese Herbal Preparations Regulating Intestinal Flora on Lipid Metabolism Disorders in Patients: A Meta-Analysis of Controlled Clinical Studies - Gong, Wenqian; Zhang, Wuguang; Chang, Chunyang (Frontiers in Surgery, 2022)
BACKGROUND Lipid metabolism disorders can damage human health, and the changes of human intestinal flora are closely related to lipid metabolism disorders, while traditional Chinese medicine can play a role in regulating intestinal flora and balancing intestinal microecology. In this meta-analysis, the role of oral preparations of traditional Chinese medicine that regulate intestinal flora in the prevention and treatment of lipid metabolism disorders was systematically evaluated.Methods The databases CBM, Pubmed, Embase, CNKI, Wanfang and Google Scholar were searched by rapid matching of keywords to obtain clinical controlled studies related to oral preparations of traditional Chinese medicines regulating intestinal flora. After screening and quality evaluation, Meta-analysis was performed using Review Manager 5.3 software.Results A total of 835 patients in 10 articles were included in the study. Meta-analysis showed that traditional Chinese medicine intervention could reduce the level of total cholesterol level in patients with abnormal lipid metabolism [MD=-0.61, 95%CI(-0.80,-0.42), P<0.00001], reduce triacylglycerol level [MD=-0.46, 95%CI(-0.60,-0.33), P<0.00001], increase high-density lipoprotein level [MD=0.25, 95%CI(0.17,0.34), P<0.00001], reduce the number of intestinal enterobacteria [MD=-0.64, 95%CI(-0.79,-0.49), P<0.00001], reduce the number of enterococci [MD=-1.14, 95%CI(-1.66,-0.63), P<0.00001], and increase the number of intestinal Lactobacillus [MD=0.41, 95%CI(0.09,0.74), P=0.01], and increased the number of intestinal bifidobacteria [MD=0.94, 95%CI(0.20,1.68), P=0.01].Discussion The application of oral preparations of traditional Chinese medicines that regulate intestinal flora in the prevention and treatment of lipid metabolism disorders can increase the colonization of beneficial bacteria in the intestine of patients, inhibit the growth of harmful bacteria, and restore the intestinal microecological balance, thus indirectly acting on the regulation of blood lipids in patients and contributing to the recovery of dyslipidemia.